2012
DOI: 10.1016/j.foodchem.2012.05.078
|View full text |Cite
|
Sign up to set email alerts
|

High antioxidant activity of coffee silverskin extracts obtained by the treatment of coffee silverskin with subcritical water

Abstract: Coffee silverskin (CS) is a thin tegument of the outer layer of green coffee beans and a major by-product of the roasting process to produce roasted coffee beans. CS extracts obtained by the treatment of CS with subcritical water at 25-270°C were investigated for their antioxidant activity using hydrophilic oxygen radical absorption capacity (H-ORAC) and DPPH radical scavenging capacity assays. The antioxidant activity increased with increasing the extraction temperature and the highest activity was observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
63
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 32 publications
(41 reference statements)
13
63
6
2
Order By: Relevance
“…Alternatively, the transformation of this by-product into valuable products for other purposes is attractive. However, few studies have been performed on the properties of CS, in particular the antioxidant capacity (Borrelli et al, 2004;Narita & Inouye, 2012;Pourfarzad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the transformation of this by-product into valuable products for other purposes is attractive. However, few studies have been performed on the properties of CS, in particular the antioxidant capacity (Borrelli et al, 2004;Narita & Inouye, 2012;Pourfarzad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to Narita and Inouye (2012), consumers generally prefer natural antioxidants to synthetic ones because of the higher safety. Recently, it has been reported that CS is a rich source of antioxidants constituents (Borrelli et al, 2004;Narita & Inouye, 2012), but to the best of our knowledge, there are no reports on the use of CS for cosmetic applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcritical water (SBW) has also been used to produce more functional products from protein. In the past decade, there has been growing interest in using SBW to extract proteins, essential oils, and bioactive components (Hassas-Roudsari et al 2009;Narita and Inouye 2012;Teo et al 2010). SBW is cost-effective, readily available almost everywhere in the world; moreover, water is chemically stable, safe, and harmless to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Also the CAF con-tent was higher than in the other extracts evaluated and, according to Rodrigues et al (2015), the antioxidant content and antimi-crobial activity is higher. Considering not only these results but also sustainability questions and other previous works regarding the antioxidant activity of these extracts, hydro-alcoholic extract seems to be the best one, being selected for the final patch test (Bresciani et al, 2014;Costa et al, 2014;Narita and Inouye, 2012).…”
Section: Extractmentioning
confidence: 82%